New Density-based Thermal Conductivity Equation for Snow - Aggarwal, R.K. (Defence Science Journal, 2009)
More than two hundred thermal conductivity measurements for different snow densities and snow types were carried out in-situ at a field research station located in greater Himalayan range of India. These measurements were carried out using a commercially available portable thermal conductivity meter. Thermal conductivity measurements were carried out on the fresh snow, equi-temperature snow, and surface hoar and temperaturegradient snow. Average thermal conductivity of snow varied from 0.08 W/mK (Fresh snow of 120 kg/m3 density) to 0.32 W/m K (Equi-temperature snow of 420 kg/m3 density). Based on these measurements, a new density-based thermal conductivity equation is proposed. Using this proposed equation, modeled snowpack temperatures showed closer agreement with the observed data as compared to the predictions based on other well-known empirical and theoretical thermal conductivity equations for snow. This study highlights the advantages and limitations of empirical based thermal conductivity equations over the complex models based on snow microstructure. Defence Science Journal, 2009, 59(2), pp.126-130, DOI:http://dx.doi.org/10.14429/dsj.59.1499